IJCM_387A: Prevalence of premenstrual syndrome among medical undergraduate & postgraduate female students in central India: a cross-sectional study - Vittal Priyanka; Thakre Sushama (Wolters Kluwer Medknow Publications, 2024)
Background: Premenstrual syndrome (PMS) is a menstrual disorder that can be described as a group of physical, behavioural, and emotional symptoms that occurs during the last week of luteal phase, which is usually the week before the mensuration. A study on PMS prevalence among different countries worldwide found that 47.8% of women have PMS. PMS is a common problem with symptoms that can negatively affect daily life. Therefore, this study aimed to determine the prevalence of Premenstrual syndrome and its severity among medical undergraduate and postgraduate female students in central India. Objectives: To estimate the prevalence of Premenstrual syndrome among medical undergraduate and postgraduate female students. To assess severity of premenstrual syndrome using the Premenstrual syndrome scale. Methods: A cross sectional study was conducted among 358 participant between the age group of 18 to 45 years. Premenstrual syndrome scale was used to assess the prevalence and severity of premenstrual syndrome. The data was analysed using SPSS software. Results: Age of the study participants range from 20 to 35 years, with mean age of 26.3±4.62 years. The mean age of menarche among participants was 12.8+0.98 years. The prevalence of PMS was 69%. There is a statistically significant association of age at menarche with premenstrual syndrome. Conclusion: The study showed that a higher proportion of medical students had PMS with majority of them having moderate symptoms. Therefore, greater attention needs to be given to PMS as part of healthcare service to improve work-life balance and productivity at work.